Peran Pancasila sebagai Kunci Harmoni dalam Keberagaman Indonesia - Gita Fariza; Syamzaimar Syamzaimar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
Indonesia is widely recognized as a diverse country with differences in ethnicity, religion, culture, and language. This diversity, while being a national strength, can also create social tension if not properly managed. In this context, Pancasila plays an essential role as a guiding principle in maintaining social harmony. This study aims to explore how Pancasila contributes to creating harmony within Indonesia’s diverse society. The research uses a qualitative descriptive approach through a literature review of recent academic sources. The findings indicate that the values of tolerance, unity, and social justice embedded in Pancasila are still relevant and influential in shaping harmonious social interactions. However, in reality, the implementation of these values has not been fully optimal, especially due to the influence of globalization and the rapid development of digital technology. This study suggests that strengthening Pancasila-based education and increasing public awareness are necessary to maintain social balance. Therefore, continuous efforts are needed so that the values of Pancasila remain alive and practiced in everyday life.